ANALISIS SENTIMEN PENGGUNA TWITTER TERHADAP PSBB DI JAKARTA MENGGUNAKAN METODE NAÏVE BAYES CLASSIFIER - Azini Fauzia Putri, (2022)
PSBB or Large-Scale Social Restrictions is one of the measures to prevent spreading COVID-19 pandemic by the government. The implementation of PSBB takes place in almost all parts of Indonesia, one of which is in the DKI Jakarta. After the PSBB ends, the Transitional PSBB begins, where there is leeway in general activities and activities that are opened by observing health protocols. Then after the implementation of the Java and Bali PPKM by the central government, a strict PSBB was imposed in Jakarta which continued to experience changes in regulations accord to situation and public conditions. In this study, an analysis of public sentiment regarding the PSBB in Jakarta was carried out through social media Twitter with Naïve Bayes Classifier method. Data for this research are tweets obtained from Twitter using the keyword "PSBB DKI Jakarta" from 1st February-31th March 2021. Final result of this research with oversampling is an accuracy value is 0.8, a recall value is 0.9318, and specificity value is 0.8.